Penerapan Corporate Social Responcibility (CSR) di TBBM Pertamina Rewulu sebagai Bentuk Pemberdayaan Masyarakat - Kanita Khoirun Nisa; Muhammad Alhada Fuadilah Habib (Prodi Sosiologi FISIP UPR, 2020)
The purpose of this study was to determine the implementation of CSR in Pertamina Rewulu TBBM. Pertamina Rewulu TBBM is located in the village of Agromulyo, Kec Sedayu, Bantul, Yogyakarta. The research method used is qualitative. The results showed that there was a form of community empowerment around Pertamina Rewulu TBBM, namely the presence of superior herbal medicine products. This empowerment program involves the community. The main target of this empowerment program are women producers and sellers of herbal medicine who are also members of the herbal medicine group Seruni Putih and JHM.